Study the Causes of Formal Change Orders and Analyze their Impact on Building Projects - Hassan, Bassam; Jrad, Fayez; Ahmad, Sonya (Latakia University Journal -Engineering Sciences Series, 2015)
Many studies have tried to determine the impact of change orders on the cost and time of the project, which in turn leads to differences and disputes between contractors and owners. Where change orders dealt with in various engineering projects. This search displays formal causes of change orders occurring during the life cycle of the project in Syrian coastal zone. Particular building projects are studied, and the most important impact on completion of the project indicators (cost_time) is discussed. Also identifies the party responsible for the change, and shows the weak points during follow the change order life cycle and provides recommendations for each of the responsible parties, stressing the need to monitor performance in order to manage change order and address the causes and impact alleviation. The prediction models were drafted at additional cost that may result from change orders.